Diplomatic negotiations and the Iran Nuclear Deal: Between the realistic and liberal paradigms - Antonia Pop (CES Working Papers, 2020)
The Joint Comprehensive Plan of Action or the Iranian Nuclear Deal was a real success of multilateral diplomacy. A transaction in the global request to stop the Iranian nuclear proliferation. The paper focuses on the United States withdraw from JCPOA and the difficulty of European Union to maintain the agreement. The research paper also proposes to answer at two key questions, which will provide as much analysis as possible on the Comprehensive Joint Action Plan. Which theory of international relations best explains the current situation of the Iranian Nuclear Agreement? What is the role of diplomacy in ratifying the agreement? The results have shown that the relationship between the Islamic Republic of Iran and the United States of America seemed to have every chance of escalating into a war, but the diplomacy is effective, while the European Union uses economic instruments to save the deal.
Keywords: 330; diplomatic negotiations; Iranian Nuclear Deal; United States; European Union